Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0102-311x00186615
|View full text |Cite
|
Sign up to set email alerts
|

Difusão espaço-tempo do dengue no Município do Rio de Janeiro, Brasil, no período de 2000-2013

Abstract: Resumo: A cidade do Rio de Janeiro, Brasil, apresenta elevado potencial de receptividade para a introdução, disseminação e persistência da transmissão de dengue. A ocupação do município conformou um mosaico heterogêneo e diversificado, com distribuição vetorial diferenciada entre e dentro dos bairros, proporcionando epidemias distintas nesta escala de observação. Este trabalho busca identificar essas epidemias e o padrão de difusão da transmissão do dengue sob a dimensão de tempo e espaço. Foi utilizado um mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
(48 reference statements)
4
22
0
11
Order By: Relevance
“…As dengue has been endemic in Rio de Janeiro for the last three decades and Janeiro has already been identified as a hot spot for dengue and as a key region for dengue diffusion. Previous studies also identified Catumbi, a neighbourhood in the Downtown area, as a high-risk location for dengue [38,39]. In our findings, Catumbi comprised the most likely chikungunya cluster, the second most likely cluster for dengue and the third most likely for Zika.…”
Section: Dengue Chikungunya and Zika Multivariate Clusterssupporting
confidence: 75%
“…As dengue has been endemic in Rio de Janeiro for the last three decades and Janeiro has already been identified as a hot spot for dengue and as a key region for dengue diffusion. Previous studies also identified Catumbi, a neighbourhood in the Downtown area, as a high-risk location for dengue [38,39]. In our findings, Catumbi comprised the most likely chikungunya cluster, the second most likely cluster for dengue and the third most likely for Zika.…”
Section: Dengue Chikungunya and Zika Multivariate Clusterssupporting
confidence: 75%
“…Using mapping techniques to study vector-borne disease epidemiology has proven crucial, as seen with previous research on dengue virus [ 15 ] and chikungunya [ 16 ]. These health geography studies can identify disease propagation patterns and high-risk areas, then model forecasts allowing inferences for the determinants of these outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Além dessa característica urbana, a sazonalidade do clima na região, marcado por uma estação seca e outra chuvosa, também influencia na dinâmica da dengue (SIQUEIRA et al,2017). Portanto, a análise do comportamento espaço-temporal da dengue é de grande importância, uma vez que, por se tratar de uma doença que tem uma forte dinâmica sazonal, é esperado que esses processos se manifestem no espaço por ondas de espalhamento, condicionadas pela mobilidade da população, sua imunização à doença, a presença do vetor e pelas condições do ambiente (XAVIER et al, 2017). Conhecer de maneira profunda a dinâmica da doença, particularmente em grandes centros urbanos, pode contribuir para as ações de controle e vigilância, otimizando recursos, apoiada pelo uso dos sistemas de informações geográficas (SIG), o que pode oferecer subsídios mais concretos, e com maior rapidez, sobre informações quantitativas e qualitativas (PETTA; NASCI-MENTO, 2000;CAIAFFA et al, 2008).…”
Section: Análise Espacial Das Ondas Epidêmicas De Dengue Por Sig No Dunclassified
“…Para a realização deste estudo, os trabalhos de Catão (2016), Caiaffa et.al (2008) e Xavier et al (2017) foram as principais referências e a partir destes foi feita a construção da metodologia. Os dados utilizados foram disponibilizados pela Secretaria de Saúde do Distrito Federal (SES-DF).…”
Section: Procedimentos Executadosunclassified
See 1 more Smart Citation